Graphene-gated lateral P–I–N photodiode based on silicon-on-insulator process. (22nd January 2016) - Zou, Wanghui; Xia, Yu; Peng, Wei; Zeng, Yun
Abstract: A lateral P–I–N photodiode consisting of a monolayer graphene gate based on the silicon-on-insulator (SOI) process for blue and ultraviolet wavelengths is proposed. The introduced gate increases the depletion area with a small gate bias voltage. Owing to the extraordinary optical and electrical properties of graphene, the gated structure shows an improved quantum efficiency over the conventional "ungated" structure. Moreover, the employment of graphene is mainly compatible with modern integrated circuit processes and makes the proposed device suitable for future integration.